Health Education for Immigrants: Improving Awareness of Early Cancer Screening through a Participatory Approach - Aditya Bhayusakti; Dayu Satria Wibawa; Dwimantoro Imam Prilistyo; Yuriske Agnovianto; Liana Faizah Aulia (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2026)
Immigrants are a vulnerable population with substantial barriers to accessing health information and medical services, including early detection of chronic diseases such as cancer. Low health literacy among immigrants may be caused by linguistic and cultural differences, uncertain legal status, and financial limitations. These conditions lead to delayed diagnosis and increased risk of cancer-related complications. Early detection through screening has been proven effective in reducing cancer mortality. For instance, colorectal cancer screening may reduce mortality risk by 35%, while mammography can decrease breast cancer mortality by 41%. However, screening coverage among immigrant populations remains low. Studies suggest that sociocultural barriers, limited knowledge, and lack of physician recommendations contribute to poor participation in cancer screening programs. This community service activity aimed to increase immigrants' knowledge of early cancer screening and health education using an interactive and participatory community-based counseling approach. A pre-experimental one-group pre-test and post-test design was employed. The program involved 14 immigrants residing in temporary shelters under the coordination of the International Organization for Migration (IOM). Participants attended a counseling session accompanied by pre- and post-intervention knowledge assessments. Results showed a 37.3% improvement in mean knowledge scores, and the paired t-test produced p = 0.0000 (p < 0.05), indicating a statistically significant difference between pre-test and post-test scores. These findings demonstrate that the counseling intervention effectively improved participants’ understanding of cancer and the importance of early detection. The activity also highlights the importance of cross-sector collaboration, especially with IOM, in developing sustainable health promotion and disease prevention programs for immigrant communities.